EFEKTIVITAS MODEL PEMBELAJARAN PBL (PROBLEM BASED LEARNING) DENGAN SOAL ANIMASI TERHADAP NILAI KOGNITIF SISWA KELAS XI SMA NEGERI 1 JABUNG - Damayanti Damayanti; Triana Asih; HRA Mulyani (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2022)
This study aimed to determine the effectiveness of the PBL (Prob1em Based Learning) model with animation questions on the cognitive values ​​of class XI students on the Human Movement System at SMAN 1 Jabung. This type of research was quasi-experimental using a non-equivalent control group design technique. The researcher used 2 sample groups, namely Class XI IPA 2 as an experimental class with 29 students using the PBL (Problem Based Learning) model with animation questions and class XI IPA 1 as a control class with 30 students using the PBL (Problem Based Learning) model. ) without animation problems. The instrument in this study used a test in the form of multiple choice questions, namely pretest and posttest. Based on the results of the study using the t-test from the post-test results of the experimental class was 78.84 and the control class 65.2 obtained tscore> t-table (17.48>2.00). Then the effectiveness of the PBL (Problem Based Learning) model with animation questions was known by the gain score in the experimental class of 0.55 (medium). The control class had a gain score of 0.32 (medium). So it can be concluded that the class that uses the PBL (Problem Based Learning) model with animation questions and the class that used the PBL (Problem Based Learning) model without the animation problem were both effective in increasing the cognitive value of the XI science class students at SMA Negeri 1 Jabung.